HarvestChoice - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
HarvestChoice is an initiative, jointly led with the University of Minnesota’s International Science and Technology Practice and Policy program, to generate knowledge products to help guide strategic investments to improve the well-being of poor people in Sub-Saharan Africa and South Asia through more productive and profitable farming.